HEAVY METAL CONTENT IN VEGETABLE GARDEN SOILS IN RELATION TO THEIR NATURAL BACKGROUND - Črnec , Katja; Strmčnik, Ana; Vrščaj, Borut (Journal of Energy Technology, 2025)
Heavy metals (HM) are present in soil naturally [1], due to the weathering of the element-rich parent rock and by anthropogenic sources (industry, energy production, agriculture, traffic) [2– 4]. The agricultural sources of increased HM concentrations in soil are HM-containing fertilizers and pesticides. Agricultural soils are often considered polluted, and are therefore subject to soil contamination monitoring for food safety reasons. Allotments are particularly at risk from intensive gardening, the general overuse of fertilizers, soil conditioners, often seen as a means of improving soil quality, in some cases the overuse or misuse of pesticides and, in the past, the use of coal ash. In some cases, landowners are also receiving untested and potentially polluted soils from elsewhere. Therefore, the soils of the vegetable/allotment gardens are generally considered to be ‘highly anthropogenized’. According to Slovenian legislation [5], the HM concentration is considered elevated if the HM concentration in the soil is above the limit immission value (LIV), polluted if it is above the warning immission value (WIV) and critically polluted if it is above the critical immission value (CIV). The HM content was analyzed in the soils of 20 allotment gardens in the village of Legen (Municipality of Slovenj Gradec, Carinthia, Slovenia). The soil samples were dried, ground and sieved in the FEP laboratory, and analyzed ‘by Bureau Veritas Commodities (Canada) using Aqua Regia extraction to determine the ’pseudo-total content’ for 37 elements (Ag, Al, As, Au, B, Ba, Bi, Ca, Cd, Co, Cr, Cu, Fe, Ga, Hg, K, La, Mg, Mn, Mo, Na, Ni, P, Pb, S, Sb, Sc, Se, Sr, Te, Th, Ti, TI, U, V, W, and Zn), 10 of which (in the frames) are considered common HM soil contaminants. The comparison of the HM concentrations in the garden soils with the well-known rich natural geochemical background of the area showed that the values for all the compared metals, except Al, Fe, Ga, Sc, Th and Co, were higher than natural element backgrounds in the Eastern Alps and in Slovenia as a whole. The HM concentrations in the garden soils were within, or slightly above, the natural background values [1], but below the LIV, with the exception of Pb and Zn in four gardens, where the concentrations exceeded the WIV [6]. The garden soils in the Legen village area have been enriched anthropogenically, most likely by the introduction of manure, and, in one case, untested and contaminated soils from elsewhere. Most of the gardens are characteristically oversupplied with the nutrients P and K; the soils are moderately enriched with soil organic matter and have an average acidity of pH 6.7, which means that the soil is neutral.